2017
DOI: 10.4103/2321-0656.193995
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey about the prevalence of food addiction among selected type 2 diabetes subjects

Abstract: Background: Plethora of studies has authenticated the linkage between overeating, overweight, and diabetes. Thus, this study was framed to evaluate whether diabetes subjects are food addicted which leads to overweight and thereby pave way for the development of type 2 diabetes. Methodolgy: The Yale Food Addiction Scale (YFAS) has been recommended for the assessment of addictive eating behavior. Result: The German version of the YFAS was administered to type 2 diabetes subjects (n = 100) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The Yale Food Addiction Scale (YFAS) was developed to assess whether individuals exhibit patterns of consumption of highly palatable food consistent with substance dependence. Based on this scale the prevalence of food addiction among Diabetic patients was reported to be 6% [8]. Almarsukka et al, (2015) [9] in a cross sectional study on food addiction among Grade I obese women reported a prevalence of 62%.…”
Section: Introductionmentioning
confidence: 99%
“…The Yale Food Addiction Scale (YFAS) was developed to assess whether individuals exhibit patterns of consumption of highly palatable food consistent with substance dependence. Based on this scale the prevalence of food addiction among Diabetic patients was reported to be 6% [8]. Almarsukka et al, (2015) [9] in a cross sectional study on food addiction among Grade I obese women reported a prevalence of 62%.…”
Section: Introductionmentioning
confidence: 99%